(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article discusses interrogation tactics of a suspect involved in illegal fishing, hunting, or other aquatic resource exploitation, necessitating the formation of specific tactical recommendations regarding the conduct of interrogations of suspects in criminal proceedings of this category. Based on an analysis of pre-trial investigation practices and scientific literature, the author proposes detailed specifications of the main provisions of interrogation tactics of suspects during the investigation of illegal fishing, hunting, or other aquatic resource exploitation. It is established that the peculiarities of interrogating a suspect during the investigation of illegal fishing, hunting, or other aquatic resource exploitation primarily depend on the situation of this investigative action. That is, whether the person wishes to testify or not. The article also distinguishes between conflict and non-conflict situations in interrogating suspects of these categories of criminal offenses. The author outlines typical investigative situations during the interrogation of suspects in the article and proposes a vision for resolving problematic situations during suspect interrogation based on an analysis of investigative practice and scientific literature. The article establishes that the successful conduct of interrogation of suspects involved in illegal fishing, hunting, or other aquatic resource exploitation is based on three main factors: a) the psychological process of forming testimonies; b) establishing contact with the person being interrogated; c) skillful application of interrogation tactics considering the situation that arises during the investigative action.